OPTIMAL TAX INVESTIGATION BASED ON THE RECOVERY OF STATE REVENUE LOSSES - Widodo, Wahyu; Darmawan, Rizki Piet (Journal of Tax Law and Policy, 2024)
This study investigates the optimal implementation of tax crime investigations aimed at safeguarding the state’s revenue interests. It emphasizes that the recovery of losses to state revenue must be the primary focus in tax crime investigations, in line with the principles of restorative justice. The study uses a normative legal approach grounded in statutory provisions, legal doctrines, and empirical data to address whether tax investigations in Indonesia reflect restorative objectives and what guiding principles may enhance their effectiveness